Dependency and Underdevelopment: The Nepalese Context - Luitel, Samira (Occasional Papers in Sociology and Anthropology, 2010)
The World Bank report (1991) mentioned that "Nepal is one of the world's poorest countries. It ranks 115th in per capita GNP out of 120 countries. With respect to life expectancy, it ranks 103rd out of 118 reporting countries. It is one of the constellations of countries characterized by rapid population increase, low or negative per capita GDP growth and a slow transition out of a subsistence agricultural economy. It exhibits many of the characteristics of similar sub-Saharan African economies, including a limited productive land base, a land-locked location, and a very low level of exports." DOI: 10.3126/opsa.v11i0.3037 Occasional Papers in Sociology and Anthropology Vol.11 2009 202-220